Increasing Critical Thinking Skills and Interest in Learning Physics for Class X High School Students through the Implementation of Problem-Based Learning - Karollina, Novi; Rahmad, M.; Ekasari, Nofita (Science Education Department of Mathematics and Natural Sciences Education Faculty of Teacher Training and Education, Universitas Riau in collaboration with the Association of Indonesian Science Educators (PPII), 2024)
The research aims to increase critical thinking skills, interest in learning physics, and alternative energy materials through the PBL model. This type of research applies classroom action research (CAR) with the subject of research being class X.5 students at SMA 4 Pekanbaru, totaling 36 students. CAR is carried out in 2 cycles with the stages of each cycle consisting of planning, action, observation, and reflection. Data collection uses observation sheets, tests of critical thinking skills, and learning interest questionnaires. Data on critical thinking skills and interest in learning were analyzed descriptively through data obtained in cycles 1 and 2. The results of the research were: 1) students' critical thinking abilities increased from cycle 1 to cycle 2, based on observation results, it increased from the sufficient category in cycle I to the good category in cycle II and test results increased from middle category in cycle I to high category in cycle II, 2) students' interest in learning increased with a score of 76.08 in cycle I to 79.75 in cycle II with the same category, namely high. It was concluded that the application of worksheet students with the PBL model was able to improve the critical thinking skills and interest in learning of class X.5 students at SMA 4 Pekanbaru in learning physics about alternative energy materials.